COMPENSATION FOR VIOLATION OF HUMAN DIGNITY IN THE PRISON SYSTEM: CIVIL LIABILITY OF THE BRAZILIAN STATE - Silvia Alves Lourenço, Cristina (Revista Gênero e Interdisciplinaridade, 2025)
The text analyzes the evolution of law after World War II, highlighting the transition from positivism to post-positivism, a movement that values ​​human dignity as a fundamental core of the legal system. It emphasizes that, despite the formalization of constitutional guarantees and international human rights treaties, the implementation of these principles faces challenges, notably in the Brazilian prison system. The article examines the civil liability of the State in the face of systematic violations of inmates’ rights, including overcrowding, unsanitary conditions, and degrading treatment, which give rise to compensation for moral damages. It also explores the role of the Supreme Federal Court in recent decisions that consolidate state accountability and propose alternatives for reparation, such as sentence reduction. Finally, it discusses the limitations of judicial activism and the need for institutional reforms to guarantee the dignity of prisoners, highlighting the insufficiency of isolated financial compensation to solve the structural problems of the prison system.